Reflections on naval warfare in the first half of the 19th century. Incorporation of steam technology and its scope in Europe and Latin America - Gutiérrez, Manuel (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
The development of naval warfare underwent a strong transformation at the beginning of the 19th century. This was due to the introduction of a new technology that allowed warships to stop being dependent on wind and ocean currents for their propulsion. The steam engine was a radical complement, which managed to eliminate many of the obstacles that limited navigation. This determined a change in the strategy of naval warfare, which led to the war fleets of the 19th Century having a decisive value in modern conflicts. Although this transformation occurred in the great powers, it also affected the nascent Latin American states that were beginning to build their navies.